The Effect of Cooling Face Therapy on Recovery from Pain for Patients after Rhinoplasty: A Randomized Controlled Clinical Trial - Hamidi, Maisam Saadoun; Kadhim, Alaa Jawad; Bahman, Aghaie (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): The present study aimed to test the effect of cooling face therapy on recovery from pain for patients after rhinoplasty.Methods: a randomized clinical trial was conducted in AL-Kindi teaching hospital and AL-Wasiti teaching hospital from 22 November ,2023 to 5 June, 2024. After the sample was selected, 53 patients were divided into two groups, an experimental group with 26 patients, and a control group with 27 patients. To achieve the purpose of study in the experimental group, a cold gel mask. pain was assessed using a Numerical Pain Scale, the interview method was chosen for data collection.Results:  The data analysis showed all patients had pain in the pre-test, while the results showed that the average pain scale post-test for the intervention group with the cold gel mask was   50% with no pain, while in the traditional care group the pain intensity was 37% with moderate pain. so, there was a highly significant difference in pain levels between the experimental and control groups at p-value < .001).Conclusion: It is concluded from the results of the study that applying a cold gel mask is effective in reducing pain after rhinoplasty compared to traditional ice compresses.Recommendations: The study recommends the use of a cold gel mask after rhinoplasty to reduce pain after rhinoplasty.